2019
DOI: 10.3390/met9020228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a New Grain Refiner (Al–Ti–Mg–Ce) on Hardness, Tensile, and Impact Properties of Al–7Si Alloy

Abstract: Through studying the effects of the Al–5Ti-x(Mg–30%Ce) refiner on the microstructure of the Al–7Si alloy, we investigated the hardness, tensile, and impact properties of the Al–Si alloy before and after refinement. The refinement results show that Mg–30%Ce can improve the refinement effect of Al–5Ti on Al–7Si, and also refine α-Al and eutectic Si in Al–7Si. When 2%Mg–30%Ce is added, the refining effect of the aluminum–silicon alloy is most obvious. After refinement, the hardness and tensile properties of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Whereas Aluminum 2219-T31 has the highest modulus of elasticity among the six aluminum alloys, which is 73.1 GPa, while Aluminum 2017-T4 has the second highest modulus of elasticity value of 72.4 GPa. Pure Aluminum has the lowest stress strength, and this is consistent with the previous statement that pure Aluminum has low strength and mechanical properties, so alloys from other materials are needed so that their mechanical properties can be improved [12], [19].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Whereas Aluminum 2219-T31 has the highest modulus of elasticity among the six aluminum alloys, which is 73.1 GPa, while Aluminum 2017-T4 has the second highest modulus of elasticity value of 72.4 GPa. Pure Aluminum has the lowest stress strength, and this is consistent with the previous statement that pure Aluminum has low strength and mechanical properties, so alloys from other materials are needed so that their mechanical properties can be improved [12], [19].…”
Section: Resultssupporting
confidence: 89%
“…Like several studies that have been done, various elements can be added to aluminum alloys to produce better materials. Some of these elements are copper (Cu), silicon (Si), zinc (Zn), manganese (Mn), magnesium (Mg), and so on [12]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, various particles and alloying elements, including Al 2 O 3 , SiC, and TiB 2 , are employed to refine and fine-tune aluminium alloy grains and surface morphology to improve the mechanical characteristics [6,7]. Grain refining can be accomplished using rapid solidification and repeated deformations, dissolving the modifiers using molten metal, lasers, and friction stir processing [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…They frequently cause defects, such as composition segregation, cracks, and shrinkage cavities. Consequently, the grain refinement addition of Al alloys to improve the mechanical properties and the microstructure of Al alloys has become a research focus 7 Kodetova´, et al 8 concluded that the addition of Sc, Zr in the hot-rolled alloys stabilizes and refines grains. The grain size was around 1000 mm in the AlZnMgCuFe and change to 20 mm in the AlZnMgCuFeScZr hot-rolled alloys.…”
Section: Introductionmentioning
confidence: 99%
“…They frequently cause defects, such as composition segregation, cracks, and shrinkage cavities. Consequently, the grain refinement addition of Al alloys to improve the mechanical properties and the microstructure of Al alloys has become a research focus 7 …”
Section: Introductionmentioning
confidence: 99%